Rub-Impact Detection in Rotor Systems with Pedestal Looseness Using a Nonlinearity Evaluation - Mian Jiang; Yingwei Kuang; Jigang Wu; Xuejun Li (Shock and Vibration)
In this paper, a nonlinearity evaluation is proposed in order to identify the rub-impact in rotor systems with pedestal looseness. Nonlinear mathematical models have been established for bearing-rotor systems with single pedestal looseness and pedestal looseness coupled with rub-impact. Piecewise linear stiffness and damping are considered regarding the position of pedestal looseness, while radial impact forces are defined using the Colulomb type of frictional relationship during rub-impact. The nonlinearity evaluation is employed to quantify the nonlinearity of the dynamics of bearing-rotor systems, which are calculated at different looseness clearances. The experiments for rotor systems with pure pedestal looseness and pedestal looseness coupled with rub-impact are conducted respectively to collect the vibration signals on different looseness clearances. Two different curves are obtained using the nonlinear fitting method for the values of nonlinearity evaluation. The rub-impact within rotor systems with pedestal looseness can then be identified by comparing the curves that denote the trend of nonlinearity evaluation for the measured vibration responses.